2022
DOI: 10.3390/ijms23073480
|View full text |Cite
|
Sign up to set email alerts
|

The Next Frontier: Translational Development of Ubiquitination, SUMOylation, and NEDDylation in Cancer

Abstract: Post-translational modifications of proteins ensure optimized cellular processes, including proteostasis, regulated signaling, cell survival, and stress adaptation to maintain a balanced homeostatic state. Abnormal post-translational modifications are associated with cellular dysfunction and the occurrence of life-threatening diseases, such as cancer and neurodegenerative diseases. Therefore, some of the frequently seen protein modifications have been used as disease markers, while others are targeted for deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 191 publications
0
13
0
Order By: Relevance
“…The processes underpinning tumor susceptibility to UB/UBL modifications have been the focus of significant investigation in recent years, 27 GSVA studies found that crucial biological pathways and processes like MTORC1 and MYC were enriched. Yan's research found that SUMOylation of AMPK1 reduces AMPK activity primarily for mTORC1 signaling 28 .…”
Section: Discussionmentioning
confidence: 99%
“…The processes underpinning tumor susceptibility to UB/UBL modifications have been the focus of significant investigation in recent years, 27 GSVA studies found that crucial biological pathways and processes like MTORC1 and MYC were enriched. Yan's research found that SUMOylation of AMPK1 reduces AMPK activity primarily for mTORC1 signaling 28 .…”
Section: Discussionmentioning
confidence: 99%
“…MLN4924 is undergoing several clinical studies to evaluate its anticancer effects on solid tumors and leukemia. Five phase I clinical trials have been completed, suggesting that MLN4924 alone or in combination with chemotherapy is safe and shows effective therapeutic effects [ 40 ]. Moreover, the potential anticancer mechanism of MLN4924 is its inhibitory effect on NAE activity by binding to NAE to produce a covalent NEDD8-MLN4924-adduct [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…This system constitutes the ubiquitin–proteasome system (UPS). UPS is the major protein hydrolysis control system in cells, which regulates the clearance of misfolded and aggregated proteins and most excess produced normal proteins [ 17 ].…”
Section: Ub and Ublsmentioning
confidence: 99%